Gandrung Banyuwangi: Kontestasi dan Representasi Identitas Using - Novi Anoegrajekti (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
The article wants to emphasize contestation among authorities in understanding gandrung as identity construction that increased since 2000 until 2005. Blambangan Art Council and bureaucracy, for example, tried to increase Using identity through political policies. By using hegemony perspective, especially in the concept of contestation among residual, dominant, and emergent culture, I will analyze (1) the process of the contestation for gandrung among bureaucracy, santri, and capitalist in the context of representation of Using identity based on socio-cultural powers of each authority in particular times and spaces and (2) the power position of each authority in crafting hegemony towards gandrung. As something constructed, cultural identity is discursive, fractured, and dynamic based on times and spaces. Representation of Using identity is a battle-field in a cultural political project.